Antioxidant and Anti-Inflammatory Effects of Blueberry Anthocyanins on High Glucose-Induced Human Retinal Capillary Endothelial Cells - Zhou, Jianzhong; Ma, Yanhong; Li, D. J.; Yan, Zheng; Huang, Wuyang; Sui, Zhongquan (Oxidative medicine and cellular longevity, 2018)
Blueberries possess abundant anthocyanins, which benefit eye health. The purpose of this study was to explore the protective functional role of blueberry anthocyanin extract (BAE) and its predominant constituents, malvidin (Mv), malvidin-3-glucoside (Mv-3-glc), and malvidin-3-galactoside (Mv-3-gal), on high glucose- (HG-) induced injury in human retinal capillary endothelial cells (HRCECs). The results showed that BAE, Mv, Mv-3-glc, and Mv-3-gal enhanced cell viability (P<0.05 versus the HG group at 24 h); decreased the reactive oxygen species (ROS, P<0.01 versus the HG group both at 24 and 48 h); and increased the enzyme activity of catalase (CAT) and superoxide dismutase (SOD) (P<0.05 versus the HG group both at 24 and 48 h). Mv could greatly inhibit HG-induced Nox4 expression both at 24 and 48 h (P<0.05), while BAE and Mv-3-gal downregulated Nox4 only at 48 h (P<0.05). Mv, Mv-3-glc, and Mv-3-gal also changed nitric oxide (NO) levels (P<0.05). BAE and Mv-3-glc also influenced angiogenesis by decreasing the vascular endothelial cell growth factor (VEGF) level and inhibiting Akt pathway (P<0.05). Moreover, Mv and Mv-3-glc inhibited HG-induced intercellular adhesion molecule-1 (ICAM-1, P<0.001) and nuclear factor-kappa B (NF-κB) (P<0.05). It indicated that blueberry anthocyanins protected HRCECs via antioxidant and anti-inflammatory mechanisms, which could be promising molecules for the development of nutraceuticals to prevent diabetic retinopathy.